Tubercular osteomyelitis of the lateral-third of the clavicle. (14th January 2016) - Pal, Chandra Prakash; Kumar, Harish; Kumar, Suneel; Hussain, Asif
Abstract : An elderly women with a chronic history of pain and swelling of the right clavicle was investigated. She also had constitutional symptoms. Clinical examination showed mild inflammatory signs over the lateral one-third of the clavicle and the swelling was hard. Clavicle X-ray showed a lytic lesion in the lateral-third of the clavicle and MRI revealed a focal hyperintense area with cortical breach involving the superior cortex of the clavicle. The diagnosis was confirmed as tubercular osteomyelitis after the biopsy, which showed chronic granulomatous inflammation, and the culture was positive for Mycobacterium tuberculosis . Pain resolved by 6 weeks, swelling by 4 months and complete radiological resolution was seen at 15 months after the initiation of antitubercular therapy. No deficit in function was seen. No relapse was noted at 1-year follow-up.